Melanoma inhibitory activity, a biomarker related to chondrocyte anabolism, is reversibly suppressed by proinflammatory cytokines in rheumatoid arthritis. Issue 6 (16th July 2008) - Vandooren, B; Cantaert, T; van Lierop, M-J; Bos, E; De Rycke, L; Veys, E M; De Keyser, F; Bresnihan, B; Luyten, F P; Verdonk, P C; Tak, P P; Boots, A H; et al.
Abstract : Objective: In mice, melanoma inhibitory activity (MIA) is a chondrocyte-specific molecule with similar regulation to collagen type II. As MIA is a small secreted protein, its value as cartilage biomarker in human inflammatory arthritis was assessed. Methods: MIA tissue distribution was studied by quantitative PCR and immunohistochemistry. The regulation of MIA production was studied in vivo in rheumatoid arthritis (RA) (n = 37) and spondyloarthritis (SpA) (n = 30) synovial fluid (SF), and in vitro in alginate embedded human chondrocytes. Therapeutic modulation of serum MIA was evaluated during tumour necrosis factor (TNF)α and interleukin (IL)1 blockade in RA. Results: MIA was primarily expressed by chondrocytes in the human joint. SF MIA levels were lower in RA than in SpA despite similar levels of overall synovial inflammation. Further analysis indicated that these levels were inversely correlated with the degree of joint inflammation in RA, but not in SpA, and that the levels of TNFα and IL1β were significantly increased in RA versus SpA. Accordingly, these proinflammatory cytokines suppressed MIA mRNA and protein in cultured chondrocytes. This suppression was paralleled by suppression of cartilage anabolism as assessed by collagen type 2 and aggrecan mRNA. Treatment of patients with RA with TNF blockade or IL1 blockade induced an increase of serum MIA levels. Conclusion: The decreased levels of MIA in the inflamed RA joint and the coregulation of MIA and cartilage matrix molecules by proinflammatory cytokines indicate that joint inflammation in RA not only drives accelerated cartilage degradation but also suppresses cartilage anabolism. This inflammation-driven suppression is reversible in vivo.